Clinical and radiographic features of adenomatoid odontogenic tumour - Madiyal Ananya; Ajila Vidya; Hegde Shruthi; Babu Subhas G. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2016)
Introduction: Adenomatoid odontogenic tumour (AOT) is an uncommon, non-aggressive tumour arising from the odontogenic epithelium. It accounts for 3-7% of all odontogenic tumors. The objective of this systematic review was to determine the recent trends in the clinical and radiographic features of AOT. We conducted a comprehensive literature search regarding AOT in PubMed database over the last ten years using suitable search words. Out of 57 articles of AOT, 35 met the study criteria and were included in the review. The results our review results showed that the mandibular posterior region was the commonest site for the occurrence of AOT. This is contrary to the existing literature data which state that AOT is commonest in the maxillary anterior region. This review provides valuable information and update regarding the demographic details, clinical, radiographic and histologic features of AOT.